Artistic Urban Interventions, Informality and Public Sphere: Research Insights from Ephemeral Urban Appropriations on a Cultural District - Costa, P. (2017)
Artistic intervention in cultural districts can be an outstanding viewpoint to understand the multiple layers of uses and segregations that bring everyday life vitality to the complex organisms cities are. Urban informality contexts can be fundamental for the expression of this diversity and to liminality strategies, particularly interesting in the case of artistic intervention, as artistic creativity is often about transgression, differentiation, and, therefore, conflict. Small initiatives that develop in an informal and ephemeral way by artists who choose the city as stage for their work, exploring the ambiguous and flexible boundaries between public and private spaces are particular interesting, evidencing the usual conflicts verified on creative milieus but being also important to keep these places as vernacular as possible and to avoid gentrification processes. In this perspective, this paper aims to discuss this relation between urban interventions, informality and public sphere appropriation, analyzing the way informal artistic dynamics can contribute to urban re-vitalization and to the enhancement of real creative milieus. Drawing on a research-action based methodology the authors explore the results and impacts of three experiences of urban intervention that they developed in three consecutive years in informal urban contexts in Bairro Alto, the main cultural quarter of Lisbon, Portugal. These ephemeral artistic interventions introduced in the city new spaces of public use, performing different public and private spaces, and bringing them to the public sphere, creating also “new” zones that re-gain a utility in the city, contributing to the vitality and symbolic centrality of this area.